2018
DOI: 10.1016/j.ajoc.2018.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-functional evaluation of torpedo maculopathy with optical coherence tomography angiography and microperimetry

Abstract: PurposeTo report the case of a 13-year-old girl with torpedo maculopathy, evaluated with multimodal morpho-functional retinal imaging, including fundus photography, infra-red and blue fundus autofluorescence, swept-source optical coherence tomography (OCT), en face OCT, OCT angiography and microperimetry (MP).ObservationsOn fundus examination, a torpedo-like hypopigmented lesion was observed temporal to the fovea in the left eye. OCT showed disruption of outer retinal layers and the presence of a subretinal cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 9 publications
(19 reference statements)
2
18
1
Order By: Relevance
“…multifocal electroretinogram [mfERG] and adaptive optics ophthalmoscopy [AOO]) provide insight into retinal and vascular anatomy and function, and have just recently been used to describe torpedo lesions. 4 OCTA, mfERG and AOO have been used to investigate choroidal structure 5 retinal function, 6 and cone anatomy and density 6 , 7 in torpedo lesions. However, we report the first case of AOO, multifocal ERG, and OCTA in a torpedo lesion with vitelliform material.…”
Section: Introductionmentioning
confidence: 99%
“…multifocal electroretinogram [mfERG] and adaptive optics ophthalmoscopy [AOO]) provide insight into retinal and vascular anatomy and function, and have just recently been used to describe torpedo lesions. 4 OCTA, mfERG and AOO have been used to investigate choroidal structure 5 retinal function, 6 and cone anatomy and density 6 , 7 in torpedo lesions. However, we report the first case of AOO, multifocal ERG, and OCTA in a torpedo lesion with vitelliform material.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 9 , 12 , 13 , 14 OCT-A findings included preservation of superficial capillary plexus perfusion and flow loss in the deep capillary plexus and in the area of subretinal clefting. Grimaldi et al 13 further found reduced sensitivity on microperimetry corresponding to the area of a torpedo lesion, confirming an abnormal functional component in this clinical entity. A weakness of our current report is a lack of OCT-A and microperimetry findings to further deepen our characterization of this novel type 4 morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Fundus exam shows a hypopigmented, horizontally oriented, oval-shaped lesion in the temporal macula ( Figure 7 ). 91 , 92 Although typically unilateral, bilateral cases have been reported. 93 , 94 TM is non-progressive and spares the fovea.…”
Section: Torpedo Maculopathymentioning
confidence: 99%
“…93 , 94 TM is non-progressive and spares the fovea. 91 There have been reports of growth and change in shape. 95 , 96 While usually isolated, occasionally small, round satellite lesions temporal to the main lesion have been noted.…”
Section: Torpedo Maculopathymentioning
confidence: 99%
See 1 more Smart Citation